Risk factors of osteoporosis in elderly inpatients: A cross-sectional single-centre study - Li, Han; Sun, Tianbao; Han, Dongmei; Gong, Weiwei; Mao, Weiwei; Gan, Xianze; Shu, Dan; Zhou, Qian; Xu, Lei; Hou, Liufang; Zhou, Mingcheng; Cai, Mingwei; et al. (Frontiers in Aging, 2023)
Objective: This study aimed to identify factors significantly associated with the occurrence of osteoporosis in elderly and very elderly patients. Methods: Elderly hospitalized patients who were older than 60 years old, from the Rehabilitation Hospital from December 2019 to December 2020 were selected. Barthel index (BI), nutritional assessment, the causes of bone mineral density (BMD) reductions in elderly and elderly patients were analysed. Results: A total of 94 patients (83.56 ± 8.37 years old) were enrolled. With increasing age, the BMD of the lumbar spine, femoral neck, and femoral shaft of elderly patients significantly decreased, and the incidence of osteoporosis (OP) significantly increased. The BMD of the lumbar spine was negatively correlated with female and positively correlated with serum 25-hydroxyvitamin D levels, the difference between actual body weight and ideal body weight, and blood uric acid levels; The BMD of the femoral neck was negatively correlated with age and female, and positively correlated with height and geriatric nutrition risk index score. The BMD of the femoral shaft was negatively correlated with female and positively correlated with BI. Conclusion: With increasing age, the BMD of the lumbar spine and the femoral shaft significantly decreased, and the incidence of OP significantly increased in elderly and very elderly patients. Aric acid may protect bone health in elderly patients. Early attention to the nutritional status, exercise capacity, 25-hydroxyvitamin D level, and blood uric acid level in the elderly population can help identify high-risk elderly patients with OP..